Struktur Mitos dan Oposisi Biner dalam Cerpen Pengorbanan Sulung Karya Bagus Sulistio: Perspektif Lévi-Strauss - Aliyah Sapitri; Nadillah Nadillah; Lila Navisa; Annisa Fitri Ali; Rusli Rusli (Jurnal Bahastra, 2026)
This study aims to examine the mythical structure embedded in the short story Pengorbanan Sulung by Bagus Sulistio through Claude Lévi-Strauss’s structuralist framework. The research addresses how mythemes, binary oppositions, and myth transformations construct the narrative plot and generate meaning. The story portrays a family bound by a supernatural covenant that requires the sacrifice of the firstborn before reaching the age of twenty, reflecting a tension between human agency and metaphysical determinism. This study employs a qualitative descriptive method with textual analysis, identifying key mythemes such as covenantal birth and sacrificial obligation, as well as binary oppositions including firstborn versus youngest, human versus jinn, and compassion versus injustice. The findings reveal that the narrative structure is shaped by a network of relational meanings, in which significance emerges from the interplay between structural elements rather than isolated units. Myth transformation is evident as a realistic family conflict evolves into a mystical revelation concerning the destiny of the firstborn. This study contributes a novel perspective by applying Lévi-Strauss’s structuralism to contemporary short fiction, particularly within the intersection of familial and mystical themes.